2020
DOI: 10.1101/2020.01.31.928648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic clocks predict prevalence and incidence of leading causes of death and disease burden

Abstract: Individuals of the same chronological age display different rates of biological ageing. A number of measures of biological age have been proposed which harness age-related changes in DNA methylation profiles. These include methylation-based predictors of chronological age (HorvathAge, HannumAge), all-cause mortality (DNAm PhenoAge, DNAm GrimAge) and telomere length (DNAm Telomere Length). In this study, we test the association between these epigenetic markers of ageing and the prevalence and incidence of the l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…All the utilized epigenetic aging acceleration measures have been shown to predict mortality and morbidity risk, but DNAm GrimAge acceleration stands out in the prediction accuracy ( 12 , 28 , 29 ). Previous studies have shown that DNAm GrimAge may capture the stimulus of a variety of health- and lifestyle-related factors ( 12 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the utilized epigenetic aging acceleration measures have been shown to predict mortality and morbidity risk, but DNAm GrimAge acceleration stands out in the prediction accuracy ( 12 , 28 , 29 ). Previous studies have shown that DNAm GrimAge may capture the stimulus of a variety of health- and lifestyle-related factors ( 12 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that risk-based biological age predictors often outperform chronological agebased estimations in tasks involving associations with risks of death, lifestyles, and diseases 27,28,43 . This may explain a stronger GrimAge association but non-significant associations of unhealthy lifestyles such as smoking (both overall and in disease-free population), and the future incidence of chronic diseases in healthy subjects [27][28][29]31,32,37,38,40 . In this work, we also established the association of BAA with the risk of non-chronic diseases, such as COVID-19 and the corresponding case fatality in the UKBB cohort independently of disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Two such predictors, termed PhenoAge (a DNAm predictor trained on a measure that itself was trained on mortality, using 42 clinical measures and age as input features) and GrimAge (trained on mortality, including a DNAm measure of smoking as a constituent part), outperform both Hannum and Horvath clocks in predicting mortality, and are associated with various measures of morbidity and lifestyle factors [15,16]. DNAm GrimAge outperforms PhenoAge and the first generation of epigenetic clocks when it comes to predicting time to death [8,17,18].…”
Section: Introductionmentioning
confidence: 99%